Determining the Mental Images of Fourth Grade Private and Public School Students for Science Learning Environments by Drawing Technique - Sina Şavlı; Mustafa Doğru (Universitas Pendidikan Indonesia, 2022)
The study aims to examine fourth-grade private and public-school students’ images of the science learning environment using their drawings. The survey was conducted in the 2017-2018 academic year, and a descriptive survey model was used. Participant group of this study consist of 357 fourth-grade students. In this study, data were collected by drawing technique. Content analysis, percentage, frequency, and Chi-Square test of independence were used in data analysis. Regarding the study results, although the learning environment in both schools consists of traditional classrooms and laboratories, differences were observed in student drawings according to school type (public-private). The private school students use the laboratory in science lessons, whereas the students in the public school use the teacher's desk as the experiment table. Another significant result of the study is that public-school students' priority is understanding the topic. In contrast, private school students assign more importance to the materials. Regarding the independence test results, Founding student behavior, teacher behavior, teacher position, and teaching method to differ in student images according to school type. But no found a significant difference between the place theme images of public school and private school students